Neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and their association with the severity of depression and as biomarkers for suicidal behaviour among patients diagnosed with depression - Swathi; Niranjan Hebbar YR; Soumya G Hegde; Tintu Mathew (Journal of Krishna Institute of Medical Sciences University, 2023)
Background: Depression has a significant impact on a person's quality of life and is a leading cause of death by suicide. Growing evidence points to a function for the immune and inflammatory systems in the pathophysiology of depression. Studies have shown that Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) are positively associated with depression severity and may be peripheral biomarkers of suicidal behaviour in depressed patients. Aim and Objectives: To find out NLR, and PLR values in patients with depression and their association with the severity of depression and to test their validity as biomarkers for suicidality. Material and Methods: Our study population consisted of 150 patients with diagnosed depressive disorder. Patients were evaluated with the Hamilton Depression Rating Scale (HAM-D). Patients were classified into 3 groups according to their HAM-D score such as mild, moderate and severe depression. NLR and PLR values were estimated. Results: Patients with higher HAM-D score had significantly higher NLR and PLR levels compared to patients with lower HAM-D score. NLR and PLR values were substantially higher for the suicide attempters group than the non-suicide attempters. The optimal cut off value for NLR in predicting the risk for suicide attempt was 1.96 with sensitivity of 75%, and specificity of 74%. Conclusion: Our data suggest that NLR and PLR values may be considered as easily accessible and cost-effective strategies to determine suicide risk in depression.